VD_FINDINFO HC / 2015 / 583 vom 24. Juni 2015 - VD Tribunal cantonal (2015)
DÉCISION DE RENVOI, PREMIÈRE INSTANCE, TRIBUNAL FÉDÉRAL, CONSTATATION DES FAITS | 107 al. 2 LTF, 318 al. 1 let. c ch. 1 CPC (CH), 318 al. 1 let. c ch. 2 CPC (CH)